Strategi Komunikasi Interpersonal Staf Bioskop dalam Mengelola Ekspektasi dan Keluhan Penonton (Studi Kasus di Bioskop XXI Galaxy Mall) - Dessy Nur Mustika Sari (SENTRI: Jurnal Riset Ilmiah, 2025)
This research aims to analyze the interpersonal communication strategies implemented by the staff of XXI Galaxy Mall Cinema in managing audience expectations and complaints. Using a qualitative descriptive approach, this study collects data through in-depth interviews, direct observations, and documentation of audience complaints. The results show that cinema staff use various communication techniques such as empathy, patience, and clarity in providing information to the audience and handling their complaints. However, challenges such as limited communication skills, differences in expectations between the audience and staff, and external factors such as audience congestion and limited facilities remain obstacles. To address these challenges, the cinema implements intensive communication training and utilizes technology to improve communication efficiency between staff and the audience. This study provides valuable insights into the role of interpersonal communication in enhancing customer service quality in cinemas.